Analisis Program Corporate Social Responsibility PT. X Regional Jawa Barat - Felicetiani Safrida; Riza Hernawati (UNISBA Press, 2021)
Abstract. Corporate Social Responsibility is a company obligation that must be carried out as a form of responsibility to the community. In addition, this activity is part of a business strategy in which there is a form of company concern for improving welfare. CSR can be done through various sectors, one of which is education. With the Covid-19 pandemic, learning activities have been hampered. Therefore, PT. West Java Regional X carries out CSR activities in the field of education through the